Multiple Meanings of Address Terms in Bicoli Language, South Maba, East Halmahera - Kalasun Ismail; Nurprihatina Hasan; Maricar, Farida; Sulmi Magfirah (CV. Eureka Murakabi Abadi, 2024)
Multiple Meanings of Address Terms in Bicoli Language, South Maba, East Halmahera. This research aims to determine the use of the term of address which has multiple meanings, especially in Bicoli village. Two research problems are postulated, namely the kinds of terms of address used in the Bicoli language, and the context of the terms of address used by speakers in communication. The study uses semantic theory approach to make it easier for the researcher to observe terms of address that have multiple meanings in the context of everyday conversation. The method in this study is a qualitative descriptive method which not only uses primary data in research, but also uses secondary data as a form of supporting data to strengthen the results of this study. Based on the results of the research conducted, it is found that the terms of address that have multiple meanings, such as; aye, legaya, nyangan, aremag, tamay, balo, doliu, del, monmenoy, melofo. The contexts that make the multiple meanings of the term of address are the individual context, the object context, and the mood context. Instances of the different meanings are found and identified based on these three contexts.